Czesław Miłosz and Jerzy Andrzejewski: The Holocaust as Catholic Moral Crisis - Brenner, Rachel (Poznańskie Studia Slawistyczne, 2019)
This article examines the wartime texts produced by two deeply believing Catholics – Jerzy Andrzejewski and Czesław Miłosz. In 1942, at the time of the deportations to Treblinka, these young but already prominent Warsaw men of letters and believing Catholics engaged in a correspondence which examined the ethical crisis of the Jewish genocide and its impact on Christian humanism. Miłosz and Andrzejewski followed their epistolary exchange with literary responses to the 1943 Ghetto Uprising. Whereas the letters conceptualized possibilities of moral restoration, the literary works – Miłosz’s two poems, Campo di Fiori and Biedny Chrześjanin patrzy na getto (A Poor Christian Looks at the Ghetto) and Andrzejewski’s novella Wielki Tydzień (Holy Week) – focused on the devastating impact of the Jewish genocide on their Polish Catholic world. These literary works see the event of the Holocaust as an irrevocable failure of the Catholic dogmas of caritas and love for the Other.